Sustainability reporting in Central and Eastern European companies : international empirical insights - Horváth, Péter; Pütter, Judith M. (MIR series in international business., 2017)
This collection of expert articles highlights the standards and practices concerning sustainability reporting among companies in Central and Eastern Europe (CEE). Due to the growing interest in corporate social responsibility issues, sustainability reporting has become increasingly common among businesses that claim to adhere to certain social, environmental and economic standards. While it can be observed that sustainability reporting is widely practiced in Western and Northern European countries, only few studies have been conducted on this topic in the CEE region. Drawing on a major empirical study involving researchers from 10 different CEE countries, this book addresses the status quo of sustainability reporting, outlines future prospects and provides essential recommendations for practitioners.